A Target-Oriented Data Envelopment Analysis for Energy-Environment Efficiency Improvement in Japan - Soushi Suzuki; Peter Nijkamp; Piet Rietveld (European Regional Science Association (ERSA), 2013)
This paper aims to offer a quantitative contribution to energy-environment policy in Japan in the aftermath of the Fukushima nuclear power accident. In the meantime, nuclear power supply has almost entirely been banned, with the consequence that an intensive search for alternative forms of energy supply has started (ranging from fossil fuels to renewable forms of energy, such as solar or thermal power). There is no unambiguous energy policy direction, as each option involves costs and CO2 consequences. Thus, a balanced energy-environment policy is difficult to achieve in the short run. Japan has even withdrawn from the Kyoto protocol. There is an urgent need for a comprehensive efficiency and performance analysis of the Japanese energy sector. A popular standard tool to judge the efficiency or performance of a Decision Making Unit (DMU) is Data Envelopment Analysis (DEA). The existence of multiple efficiency improvement solutions has in recent years prompted much criticism. In the meantime, much progress has been made to extend this approach in several directions. An example is the Euclidean Distance Minimization (EDM) method, based on a generalized distance friction function, which serves to improve a DMUfs performance by tracing the most appropriate movement towards the efficiency frontier. The EDM model is able to calculate an optimal input reduction value and an output increase value so as to reach an efficiency score of 1.0, even though in reality this may be hard to achieve for low-efficiency DMUs. In contrast, high-efficiency DMUs may find it easier to reach an efficiency score of 1.0, or, - in case of Super-Efficiency DEA - even above 1.0. This paper aims to present a newly developed, adjusted DEA model - emerging from a blend of EDM and Target-Oriented (TO) approach on the basis of a Super- Efficiency model - for generating an appropriate efficiency-improving projection model. The TO approach specifies a Target-Efficiency Score (TES) for inefficient DMUs. This approach can compute an input reduction value and an output increase value in order to achieve a higher TES. The above-mentioned TO-EDM model will next be applied to an efficiency analysis of the energy-environment interface for ten regions in Japan. The main focus will be on two input cost criteria (viz. expenditures and CO2 emission) and two output performance criteria (viz. electricity generation and regional CO2 absorption). Based on an extensive database, a comparative performance analysis of the ten Japan regions under consideration will be pursued.
Keywords: 330; Data Envelopment Analysis; Euclidean Distance Minimization; Target-Oriented; Energy-Environment efficiency